2022
DOI: 10.3126/jngmc.v20i1.48105
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Child-Pugh Classification with Esophageal Varices in Patients with Liver Cirrhosis

Abstract: Introduction: The severity of the chronic liver disease can be assessed by several non-invasive methods one of them includes scoring system like Child-Pugh classification. Aims: The objective of this study was to assess the correlation of Child Pugh class with esophageal varices in patients with liver cirrhosis. Methods: This was a cross-sectional hospital-based study of 406 patients with liver cirrhosis. Demographic and relevant clinical data were collected using a standardized questionnaire. Abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These include models for end-stage liver disease (MELD) and Child-Pugh class score (CPC). 11 Based on the CPC score, this study found the most prevalent class for Child-Pugh overall was class A (74.6%). This finding was similar to a study from Sulaiman et al where Child-Pugh A became the most characteristic subject with about 49% of patients, followed by Child-Pugh B and C with 27% and 24% patients respectively.…”
Section: Discussionmentioning
confidence: 66%
“…These include models for end-stage liver disease (MELD) and Child-Pugh class score (CPC). 11 Based on the CPC score, this study found the most prevalent class for Child-Pugh overall was class A (74.6%). This finding was similar to a study from Sulaiman et al where Child-Pugh A became the most characteristic subject with about 49% of patients, followed by Child-Pugh B and C with 27% and 24% patients respectively.…”
Section: Discussionmentioning
confidence: 66%